The collapse of representations: emerging theoretical and practical confrontations (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Since the last century, a sharp crisis in scenic representations has emerged and deepened, problematizing the old practical and theoretical matrices mobilized to produce a certain theatricality. A process that, since the 1960s, has spread from computer and numerical logic and, equally, from sociocultural movements associated with identities and decolonial actions. Repositioning scenic theories based on these other bases becomes an urgent task in the face of this convulsed set of disruptive agencies.
Keywords: performing arts; numerical technologies; representation crisis; theoretical divergences; digital performances